Eunicidae (Polychaeta) species in and around İskenderun Bay (Levantine Sea, Eastern Mediterranean) with a new alien species for the Mediterranean Sea and a re-description of Lysidice collaris - Şahin G. K. & Çinar, M. E. (Turkish Journal of Zoology, 2009)
This study comprises the Eunicidae (Polychaeta) species from Iskenderun Bay and surrounding waters (Levantine Sea, Eastern Mediterranean). Benthic material was obtained from 25 stations from 0 to 100 m depths in September 2005. Ten species and 639 individuals belonging to 5 genera were found. Most of the individuals (65%) were determined among rocks and algae. Palola valida for the Mediterranean Sea, Eunice antennata and Lysidice margaritacea for the Levantine Sea, and E. vittata, Marphysa bellii, and M. sanguinea for the Levantine coast of Turkey are new records. Eunice antennata and P. valida were introduced from the Red Sea and appear to have been well established in the area, constituting 57% of eunicids inhabiting crevices of rocks. Lysidice collaris is re-described on the basis of type material, and E. antennata, L. margaritacea, and P. valida are fully described.